2018
DOI: 10.2147/jpr.s163438
|View full text |Cite
|
Sign up to set email alerts
|

Do laws impact opioids consumption? A breakpoint analysis based on Italian sales data

Abstract: PurposeIn Italy, where the adoption of opioid analgesics in pain management has been historically poor, an increase in opioids consumption occurred between 2000 and 2015. The aim of this study is to assess, through specific time series analyses for trend changes, the impact of different intervening factors – such as the availability of new drugs, the observance of clinical guidelines, changes in prescription regulations, and in reimbursement policies – on opioids sales to community pharmacies in Italy, focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The trend in opioid use in Italy may be related to a law passed in 2010 known as Law 38/2010 in which the Italian government commits to improving the access to palliative care and pain relief. While a recently published study using data from pharmacy sales on a national level confirmed a relative increase in opioid use in Italy from 2000 to 2010, this study reported that opioid use is overall low; the most commonly used drug was codeine, which was used at 5 DDD per day per 1,000 persons in 2010 [23].…”
Section: Discussionmentioning
confidence: 99%
“…The trend in opioid use in Italy may be related to a law passed in 2010 known as Law 38/2010 in which the Italian government commits to improving the access to palliative care and pain relief. While a recently published study using data from pharmacy sales on a national level confirmed a relative increase in opioid use in Italy from 2000 to 2010, this study reported that opioid use is overall low; the most commonly used drug was codeine, which was used at 5 DDD per day per 1,000 persons in 2010 [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there are regional inequalities of opioid prescribing, e.g. in different regions in Italy (Musazzi et al., 2018) and the United Kingdom (Curtis et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 In addition, the results suggest a tendency towards prescribing increasing treatment durations and/or higher strengths or doses of strong opioids to males compared to females (Table S3), similar to findings by Campbell et al 39 There was an increase in the prescribing of transdermal strong opioids between 2010 and 2019, comparable to observations from studies in France, Germany and Italy. [21][22][23] This trend is likely due to the ease of use and convenience afforded by these formulations and the reduction in gastrointestinal side-effects compared to oral strong opioids. The oral route of administration was the most commonly prescribed, in keeping with many clinical guidelines, [42][43][44] while the use of parenteral and transmucosal formulations was low.…”
Section: Discussionmentioning
confidence: 99%
“…9,18,20 In terms of route of administration, many studies have reported increases in utilisation of transdermal opioid formulations. [21][22][23] Regarding demographic factors, the literature would suggest a higher prescribing prevalence of strong opioids in female patients and in older age groups. 8,24,25 This study aimed to determine the pattern of strong opioid prescribing in Ireland over a 10-year period from 2010 to 2019, using a national administrative pharmacy claims database.…”
Section: Introductionmentioning
confidence: 99%